Festival of ideas: Faculty of Medicine and Hospital Al-Sultan Abdullah, UiTM, participate in prestigious Ministry of Education event - Ariffin, Farnaza @ Farnaz; Ismail, Nurhuda (Faculty of Medicine, 2025)
The Festival of Ideas (FOI) is an event organized by the Ministry of Education Malaysia to celebrate innovative concepts that align with the advancement of higher education during the Industrial Revolution 4.0. The inaugural event took place from November 27 to 29, 2024, and is intended to be an annual gathering aimed at promoting higher education among Malaysians. The festival involves numerous public and private universities showcasing their programs and activities to the public. It targets individuals from all walks of life, particularly potential students looking to pursue certifications, diplomas, or degrees in various fields across the country.